Bitcoin and Blockchain to Indonesia’s Economic Resilience: A Business Intelligence Analysis - Samputra, Palupi Lindiasari; Putra, Septia Zul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
Blockchain technology has been a phenomenal discovery since its use on Bitcoin, a crypto currency created by Satoshi Nakamoto. Featuring decentralization, it allows Bitcoin to escape the interference of third parties and governments. Departing from Keynesian Theory, this study used a mixed quantitative and qualitative approach. The econometric quantitative approach uses the Vector Error Correction Model (VECM) modeling to predict the impact of Bitcoin investment on Indonesia's transaction of capital. A qualitative approach is used to analyze the LOFT effects of Bitcoin on Indonesia's economic resilience. Unlike previous studies, this study attempts to provide an explanation from the standpoint of national resilience, especially in the field of economic resilience. VECM analysis found that Bitcoin had a significant positive effect on Indonesia's transaction of capital in both the short and long terms Even though the magnitude of the influence of bitcoin is relatively small, it needs to watch out for macro performance through capital transactions. Qualitative data indicate that there is a change of Bitcoin function in Indonesia, from a payment method, into an instrument of investment. The finding explains that Bitcoin has the potential to weaken the resilience of the Indonesian economy through a reduction in the balance of payments, while Blockchain can be the main foundation of the financial industry revolution in Indonesia.